THE USE OF LESSON PLAN IN TEACHING ENGLISH AT THE ELEVENTH GRADE OF SMA N 1 AKABILURU DISTRICT - Lisa Irnia (Universitas Muhammadiyah Makassar, 2020)
This research was conducted to find out the application of lesson plan in teaching English at XI grade of SMA N 1 Kecamatan Akabiluru. The researcher found several problems on teacher’s application of lesson plans in teaching. The teachers have to create a lesson plan before teaching. Lesson plan consists of three stages; pre, while, post and the end of teaching. Although teachers created a lesson plan before teaching. The teachers still did not apply some of Pre, while, or the end in teaching subjects. It can be seen in teaching activities, the teachers used different method in every classes but the teachers used same lesson plan for every class. In this case, the teachers did not follow the learning procedures in lesson plan although it was brought in class for each meeting. This research was designed as descriptive qualitative research. The informant of this research was the teacher who teaches English in eleventh grade of SMA N 1 Akabiluru District. The research used observation and interview as technique to collect the data. First, the researcher observed the lesson plan of teachers who are teaching in class. Second, the researcher interviewed the teachers about the lesson plan when teaching in class. Based on the result of data analysis, showed that one of the two English teachers designed of lesson plan by edited the lesson plan that had been made by someone else as well both English teachers has applied all of learning procedures of lesson plan in teaching English. In different meeting, both teachers did not fully apply the whole procedures of learning activities as those are written in lesson plan. In addition, both teachers used different way of teaching. It was found that both teachers were difficult in allocating the time for each procedures.